Eculizumab and ravulizumab clinical trial and real-world pharmacovigilance of meningococcal infections across indications - Cynthia Carrillo Infante; Arshad Mujeebuddin (PLoS ONE, 2025)
Introduction Complement component 5 inhibitor therapies (C5ITs) for rare hematological, renal, and neurological diseases are associated with increased meningococcal infection risk. Robust risk mitigation measures include vaccination, drug safety programs, patient safety cards, and antibiotic prophylaxis initiation when starting C5ITs. Here we describe the exposure-adjusted meningococcal infection and mortality rates in eculizumab- or ravulizumab-treated patients based on clinical trial and real-world pharmacovigilance data. Methods Global clinical trial and real-world safety data regarding eculizumab and ravulizumab use across indications were recorded in the Alexion pharmacovigilance database. Data for eculizumab (March 2007-October 2024) and ravulizumab (December 2018-December 2024) were searched based on the Medical Dictionary for Regulatory Activities (versions 26.1, 27.0, and 27.1) High-Level Term of Neisseria infection. Only cases associated with Neisseria meningitidis were included. Reporting rates were calculated cumulatively per 100 patient-years (PY). Results At the time of analysis, cumulative exposure across clinical trial and real-world settings were 2457 and 91,052 PY, respectively, for eculizumab and 3287 and 34,582 PY, respectively, for ravulizumab. The cumulative meningococcal infection rate in clinical trials was 0.28 and 0.18 per 100 PY for eculizumab and ravulizumab, respectively. Real-world cumulative meningococcal infection rates in patients treated with eculizumab have decreased since 2007 (0.25 per 100 PY in 2024). In patients treated with ravulizumab, the real-world cumulative rate of meningococcal infection remains low (0.10 per 100 PY in 2024). The rates of meningococcal-associated mortality were ≤0.03 per 100 PY in both eculizumab- and ravulizumab-treated patients in clinical trials and real-world settings. Conclusions Meningococcal infection and mortality reporting rates have remained stable despite increasing cumulative eculizumab and ravulizumab exposure over time across indications, including rare neurological indications. Infection awareness, existing risk mitigation strategies, and availability of vaccines have effectively reduced the risk of meningococcal infections in C5IT-treated patients, underlining the importance of adhering to those measures.